LEKSIKON PERTANIAN PADA KOMUNITAS PETANI DI DESA KROMONG KABUPATEN JOMBANG KAJIAN: ETNOLINGUISTIK - Ahlan Romadhona; M. Afif Ardiansyah; Auralia Qurrata Aini; Alya Nadhifa Salsabila; Kartika Auliyah; Taswirul Afkar (Jurnal Padamu Negeri, 2026)
This study examines the agricultural lexicon used by the farming community in Kromong Village, Jombang Regency from an ethnolinguistic perspective. The research aims to describe the distinctive agricultural lexicon of the Kromong Village farming community, analyze the cultural meanings embedded within these lexicons, and identify the shift in traditional agricultural lexicons among younger generations due to agricultural modernization. This research employs a descriptive qualitative approach using linguistic ethnographic methods. Data were collected through participatory observation, in-depth interviews, elicitation, and documentation. Key informants were farmers aged 45–70 years who are native speakers of the Jombang Javanese dialect. The results show that the Kromong Village farming community possesses a rich agricultural lexicon encompassing: (1) cultivation stage lexicons, (2) traditional farming tool lexicons, (3) Javanese agricultural calendar system lexicons (pranatamangsa), (4) ritual and prayer lexicons, and (5) social relationship lexicons among farmers. (6) Shifting agricultural lexicon among young people. Each lexicon carries cultural meanings closely related to the value systems, beliefs, and local wisdom of the Jombang farming community. The study also found that most traditional agricultural lexicons are undergoing shifts or are threatened with extinction as modern technology enters and intergenerational transmission weakens.